(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
Climate change has significantly affected small island developing states in the Pacific. One of its major impacts is sea-level rise, which has reduced habitable land and forced communities to consider relocation. This study aimed to explore the issue using a qualitative-descriptive approach by analyzing ten open access documents. The research focused on how relocation has been framed as an existential threat, how local communities responded, and the extent of international involvement. The findings indicated that mass displacement could undermine the foundations of statehood, particularly when implemented without fairness and cultural sensitivity. Therefore, legal recognition for landless states and international collaboration are needed to ensure the continued existence of nations facing the frontline of the climate crisis.